ASSET AND LIABILITY MANAGEMENT DI BANK SYARIAH INDONESIA (STUDY KOMPARATIF SEBELUM DAN SESUDAH MARGER) - Kharisma, Nia Noviana Dwi; Rahmatika, Arivatu Ni'mati (Universitas KH. A. Wahab Hasbullah, 2021)
Management of liability assets must be managed properly and correctly by using the right method, so that banks can obtain greater profits in a lawful way, without strangling customers. Therefore, this study was conducted to determine the alma of Islamic banks in Indonesia before and after the merger. This research was conducted on three large banks that have merged into one, namely Bank Syariah Indonesia with qualitative methods, data collection through library research, namely library research. In the management of Liquidity and Capital Management in conventional banks, the value is greater than the management of Liquidity in Islamic banks. Meanwhile, in asset liability management, price management, Islamic banks have a higher level of price management than conventional banks. Post-merger in Indonesian Islamic banks is a very significant determining factor. , because if there is accumulation of optimal input is expected to provide maximum output as well so that efficiency occurs. On February 1, at the beginning of its operations, BSI was able to become a magnet for business players and investors in the stock market as indicated by a significant increase in share value. As of December 2020, BSI's assets have reached Rp239.56 trillion.